Women’s Broker Role in Increasing the Economy of Household: A Case Study in West Halmahera District, North Maluku - Musdhalifah Kholil; Zakeus Dadi; Yunita (Sangia Research Media and Publishing, 2023)
Household worse economic such as kopra down price, lack of household economic due to increasing of household necessary and high up life demand encouraged the women became brokers of holticultura commodity (fruits and vegetable) in West Halmahera district in order to support the family economy. The riset aimed to recognize woman role in increasing domestic economy and analysis contribution of women’s income. The sample are 25 women broker’s or dibo-dibo of horticultural commodity in East Sahu and Jailolo district West Halmahera Regency. The schedule was carried out from March to April 2022. The approach method was descriptive quantitative. The final results were that the role in increasing household economics was (1.) The women’s role in reproductive activities is role as housewives. (2.) Productive activities, that is, work to earn a living as a retailer of holticultura products (fruits and vegetables). The second objective shows that the contribution of women’s income ranges from 60% to 70% and is considered a high category. Based on the result of this research, it is suggested that women encourage participation in development programmes and increase women’s knowledge and skills to achieve a greater result and can increase their income and also be beneficial to household welfare.